2024
DOI: 10.3389/fpls.2023.1273029
|View full text |Cite
|
Sign up to set email alerts
|

DIC-Transformer: interpretation of plant disease classification results using image caption generation technology

Qingtian Zeng,
Jian Sun,
Shansong Wang

Abstract: Disease image classification systems play a crucial role in identifying disease categories in the field of agricultural diseases. However, current plant disease image classification methods can only predict the disease category and do not offer explanations for the characteristics of the predicted disease images. Due to the current situation, this paper employed image description generation technology to produce distinct descriptions for different plant disease categories. A two-stage model called DIC-Transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Comparative analysis against state-of-the-art models revealed that the improved MobileNetV2 surpassed its counterparts in terms of accuracy, recall, F1 score, and overall accuracy. Zeng et al (2024) proposed the DIC-Transformer model, which first detects disease areas using Faster R-CNN combined with Swin Transformer and generates disease image feature vectors, then employs a Transformer to generate image descriptions, enhancing subsequent classifier decoder performance through weighted fusion of text features with image feature vectors. Experiments showed that DIC-Transformer outperforms other comparative models in both classification and description generation tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative analysis against state-of-the-art models revealed that the improved MobileNetV2 surpassed its counterparts in terms of accuracy, recall, F1 score, and overall accuracy. Zeng et al (2024) proposed the DIC-Transformer model, which first detects disease areas using Faster R-CNN combined with Swin Transformer and generates disease image feature vectors, then employs a Transformer to generate image descriptions, enhancing subsequent classifier decoder performance through weighted fusion of text features with image feature vectors. Experiments showed that DIC-Transformer outperforms other comparative models in both classification and description generation tasks.…”
Section: Introductionmentioning
confidence: 99%